2014
DOI: 10.1002/jnr.23478
|View full text |Cite
|
Sign up to set email alerts
|

L‐type calcium channel blocker ameliorates diabetic encephalopathy by modulating dysregulated calcium homeostasis

Abstract: Diabetic encephalopathy is a complication of diabetes characterized by impaired cognitive functions. The objective of the present study was to examine the beneficial effect of the calcium channel blocker, nimodipine, on diabetes-induced cognitive deficits and altered calcium homeostasis in the cerebral cortex. Diabetes was induced in mice by intraperitoneal injection of streptozotocin (40 mg/kg body wt) for 5 days. Nimodipine (10 mg/kg body weight) was administered intraperitoneally to the animals every 48 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 93 publications
0
5
0
1
Order By: Relevance
“…Studies of streptozotocin (STZ)-induced diabetes in rats have demonstrated neurobehavioral deficits using the Morris water maze, which is associated with impaired hippocampal long-term potentiation [4]. The multifaceted pathogenesis of diabetic encephalopathy is not yet completely understood, but classical factors such as an imbalance in Ca 2+ homeostasis [5] may contribute to the pathology of diabetic encephalopathy. In the CNS, Ca 2+ acts as a second messenger and is known to be associated with almost every cellular event, including ion channel function, cellular proliferation and migration, neurotransmitter secretion, axon pathfinding, and dendritic outgrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of streptozotocin (STZ)-induced diabetes in rats have demonstrated neurobehavioral deficits using the Morris water maze, which is associated with impaired hippocampal long-term potentiation [4]. The multifaceted pathogenesis of diabetic encephalopathy is not yet completely understood, but classical factors such as an imbalance in Ca 2+ homeostasis [5] may contribute to the pathology of diabetic encephalopathy. In the CNS, Ca 2+ acts as a second messenger and is known to be associated with almost every cellular event, including ion channel function, cellular proliferation and migration, neurotransmitter secretion, axon pathfinding, and dendritic outgrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Недавнее исследование показало способность нимодипина не просто улучшать мозговое кровообращение пациентов после субарахноидального кровоизлияния, но и восстанавливать ишемически поврежденные нейроны и когнитивные функции [30]. Данные других исследований [31,32] свидетельствуют о том, что блокатор кальциевых каналов L-типа нимодипин полезен для предотвращения когнитивных нарушений, связанных с диабетической энцефалопатией, посредством модуляции нарушенного гомеостаза кальция. Предварительные исследования показывают, что нимодипин может также улучшать кальций-зависимые формы синаптической пластичности в гиппокампе крыс с диабетом и его введение животным с диабетом снижает выработку активных форм кислорода и перекисное окисление липидов [32].…”
Section: практическое применение блокаторов кальциевых каналов: насто...unclassified
“…For example, basolateral membrane vesicles isolated from syncytiotrophoblast of insulin-dependent diabetic patients display increased PMCA activity (359), while reduced PMCA activity or expression has been identified in parotid and submandibular salivary glands, kidney, and brain synaptosomes of streptozotocin-induced diabetic rats (260,347,421).…”
Section: Camentioning
confidence: 99%